The Evolution of Circumstellar Medium around Rotating Massive Stars - S. M. Chitã (Revista Mexicana de Astronomía y Astrofísica, 2007)
A rotating 12 M star, after its main-sequence evolution, becomes a redsupergiant when it starts core Heburning. During core helium burning, as consequence of a variation of the hydrogen shell burning eciency,the star undergoes a so called \blue loop", i.e. it evolves into a blue supergiant stage, where it nishes corehelium burning and becomes a redsupergiant again, before exploding as a supernova. We try to explain thestructures in Sher 25 and in SN 1987A through wind asymmetry caused by rotation. We use a stellar evolutionmodel to provide us with the time dependent stellar wind parameters such as wind velocity and mass-loss rate.These parameters serve as an input for hydrodynamical simulation of the circumstellar medium. The blueloop causes a very aspherical structure due to rotation, while the main sequence and redsupergiant phases arebasically spherical. We can conclude that the asymmetry of Sher 25 can be explained through stellar rotation